Multifaceted Rho GTPase Signaling at the Endomembranes - Phuyal, Santosh; Farhan, Hesso (Frontiers in Cell and Developmental Biology, 2019)
The Rho family of small GTPases orchestrates fundamental biological processes such as cell cycle progression, cell migration, and actin cytoskeleton dynamics, and their aberrant signaling is linked to numerous human diseases and disorders. Traditionally, active Rho GTPase proteins were proposed to reside and function predominantly at the plasma membrane. While this view still holds true, it is emerging that active pool of multiple Rho GTPases are in part localized to endomembranes such as endosomes and the Golgi. In this review, we will focus on the intracellular pools and discuss how their local activation contributes the shaping various cellular processes. Our main focus will be on Rho signaling from the Golgi, endosomes, mitochondria and nucleus and how they regulate proliferation, differentiation, receptor trafficking, cell migration and polarity.